A Congenital Anterior Urethrocutaneous Fistula in a Boy Whose Mother Was Exposed to Ionizing Radiations: Case Report and Literature Review - C. Spinelli; V. Pucci; C. Menchini; I. Buti; L. Fregoli; R. Spisni; A. Mogorovich (Case Reports in Urology)
Anterior congenital urethrocutaneous fistula is a rare anomaly that may present in an isolated fashion or in association with other anomalies of the genital urinary tract or anorectal malformations. A case of congenital anterior urethrocutaneous fistula nonassociated with other congenital anomalies in a 3-year-old male whose mother has been exposed to Chernobyl's nuclear fallout is described. The patient was successfully operated with no recurrence. We report a review of the literature about etiology and surgical strategy including the role of ionizing radiations. The congenital anterior urethrocutaneous fistula represents a rare malformation. The etiopathogenesis is unknown.